JENIS-JENIS GULMA PADA PADI SAWAH DI DAERAH TRANSMIGRASI PRAFI, MANOKWARI - M.J. Sadsoeitoeboen; Fajar Ria Dwi Natalia; Franssisca Souisa; Fernando Duwiri; J.P. Kilmaskossu; Carlos Kilmaskossu (Jurnal Natural, 2008)
Several weed species were observed in the rice fields of the transmigration area Prafi SP 2 during April 2006 by the State University of Papua. The weeds were classified into three groups according to their morphology characteristics, and into four groups according to their habitat. The weeds were preferred by the rice pests as host plant. Few weeds were host for the rice fields such as Echinochloa crusgalli, Echinochloa glaberescens and Pennisetum purpureum.